STATUS PERKEMBANGAN SEPEDA LISTRIK DAN MOTOR LISTRIK DI INDONESIA - Agus Surya Adi P, I Pt; Satya Kumara, I Nyoman; Raka Agung, I Gusti Agung Pt (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
The development of electric vehicles in Indonesia began in 1997 by the Indonesian Institute of Sciences (LIPI) but since 2013 has slowed down. Presidential Regulation 55/2019 strengthens the development of electric vehicles in Indonesia which followed by several supporting regulations. Currently, the development of electric vehicles, both in terms of research and industry or commercial products, is getting better. This paper reviews the current status of electric bicycles and electric motorcycles in Indonesia which are commercially available. The research was conducted by through online survey during 2020-2021 which produced a database of electric bicycles/motorcycles. Currently, there are 64 electric bicycles and 44 electric motorcycles. These vehicles use either two or three wheels with electric drive capacity between 180 W to 4200 W. The most common electric motor used is BLDC at 87%. The electric bike/motorcycle has speed ranges between 20 km/h to 70 km/h with battery capacity of 5,2 Ah to 70 Ah with milage ranging from 15 km to 200 km. The information presented will help stakeholders to get a quick overview of the development of electric bicycles/motorcycles in the country and serves as benchmark for developing electric bicycles or motor to meet domestic needs.